Vesicle Priming in a SNAP - Müller, Martin (Neuron, 2010)
In this issue of Neuron, Burgalossi et al. (2010) investigate synaptic vesicle priming using presynaptic Ca(2+) uncaging at a small, glutamatergic, central synapse. Combining this technique with mouse genetics, the authors demonstrate that vesicle priming during ongoing neural activity can be limited by the recycling of recently used SNARE complexes.